Metodología para calcular costos y beneficios ambientales del Centro de Transferencia y Transformación de Materiales - Cruz-Barahona, Cindy (Instituto Tecnológico de Costa Rica, 2019)
Currently, there is no methodology in Costa Rica to quantify the environmental benefits resulting from the management of solid waste in material transfer centers. Therefore, a methodology was developed to calculate environmental costs and benefits associated with the waste management in the Center for Transfer and Transformation of Materials (CTTM) of the Technological Institute of Costa Rica (TEC). The externalities quantified were the emissions from primary production, the emissions due to the final treatment in landfills, the consumption of water and wood for production, as well as the external costs avoided monthly for the base year 2017 product of the managing of the waste. A modification of the method for quantifying the externalities of landfills of the European Commission was used to quantify the total emissions avoided; a unit cost per m3 of water and wood consumption was assigned according to the price of the national water market of Costa Rica and the international timber market. Furthermore, a tool and a calculation guide were developed for the future use of the transfer center. The results show a monthly average of avoided emissions of 393 773,05 kg CO2eq, 26 385,97 m3 of water and 81,54 m3 of wood. The average monthly difference between the profit and the costs for the sale of the materials was calculated at $3 302,29 (USD) with an environmental gain of $33 346,17 (USD).
Proyecto Final de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnoilógico de Costa Rica, Escuela de Química, 2019
Keywords: Costos ambientales; Beneficios; Cuantificación; Centros; Transferencia; Materiales; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering